PERAN LAMA USAHA DALAM MEMODERASI PENGARUH MODAL USAHA, JUMLAH VARIASI PRODUK DAN JUMLAH PELANGGAN TERHADAP PENDAPATAN - Hartawan, Jhony; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 1 (2022): VOL 11 NO 1, JANUARI 2022 [1-403 ]DO - 10.24843/EEP.2022.v11.i01.p10, 2022)
This study aims to analyze the role of business long in moderating the influence of venture capital, the number of product variations and the number of customers on revenue. The population in this study was 82 art shop owners in Ubud District. The analysis technique used in this study is multiple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that venture capital, the number of product variations sold, the number of customers and the length of business simultaneously have a significant effect on income. Business capital, the number of product variations sold, the number of customers and the length of business have a partially positive and significant effect on income. Length of effort moderates (strengthens) the effect of venture capital on income. The length of effort to moderate (strengthen) the effect of the amount of variety of products sold on income. Length of effort moderate (strengthen) the influence of the number of customers on the owner's income. Keywords : length of business, venture capital, the number of product variations, the number of customers, income